The Detection of Fingermarks on Paper and Lottery Paper Using Ninhydrin’s Technique - seesuvan, pashrapon; Choosakoonkriang, Sirirat; Supalaknari, Supachai (วารสารวิทยาศาสตร์และเทคโนโลยี สถาบันอุดมศึกษาเอกชนแห่งประเทศไทย, 2023)
The objective of this study was to evaluate the fingermarks using the ninhydrin method. The samples studied were white A4 copy paper and Thai lottery paper. In this experiment, the samples with impressed fingermarks were kept at ambient temperature for 1, 7 and 30 days before evaluation. The quality of the developed fingermarks was evaluated from the number of minutiae detected by fingerprint examiners. It was found that the quality of the fingermarks obtained on white A4 copy paper was good enough for comparison and identification, even on the aged fingermarks deposited for 30 days. While the lottery samples tested could not yield any identifiable fingerprints on all specimens of 1, 7 and 30 days old. It was also found that the color and design of the lottery paper itself affected the quality of the developed fingermarks. Moreover, the latent fingerprints on the white copy paper can be detected with numbers of minutiae greater than 10 points even in the test items of the latent fingerprints aged for 1 year.